Wheat and rice in disease prevention and health : benefits, risks, and mechanisms of whole grains in health promotion - Watson, Ronald R. (Ronald Ross); Preedy, Victor R.; Zibadi, Sherma (Amsterdam : Elsevier/Academic Press, 2014)
Wheat and Rice in Disease Prevention and Health reviews the wide range of studies focusing on the health benefits and disease prevention associated with the consumption of wheat and rice, the two most widely consumed whole grains. This book provides researchers, clinicians, and students with a comprehensive, definitive, and up-to-date compendium on the diverse basic and translational aspects of whole grain consumption and its protective effects across human health and disease. It serves as both a resource for current researchers as well as a guide to assist those in related disciplines to enter the realm of whole grain and nutrition research. Overall, studies have shown that a decrease in the amount of whole grains in the modern diet is related to a corresponding increase in health problems that are attributed to this all-too-common dietary imbalance. The resulting health issues associated with an over-processed diet, which provides inadequate levels of nutrients from whole grains, may include obesity, diabetes, high blood lipids, chronic inflammatory states, and an excess of oxidative stress. Strength and endurance may also suffer as a result of these nutrient deficiencies, followed by declines in energy and immunity.
1. Whole wheat pasta and health / Rhanissa Hirawan, Trust Beta -- 2. Whole grain and phytate-degrading human bifidobacteria/ Juan Mario Sanz-Penella, Monika Haros -- 3. Effect of whole wheat feeding on gut function and nutrient utilization in poultry / Ahmed M. Amerah, Velmurugu Ravindran -- 4. Whole wheat in commercial poultry production / Dariusz Kokoszyki -- 5. Wheat flour in postprandial metabolic profile and health / Kristin M. Nieman, Tia M. Rains, Mary R. Dicklin, Kevin C. Maki -- 6. Bioavailability of calcium, iron, and zinc in whole wheat flour / Anwaar Ahmed, Muhammad Atif Randhawa, Muhammad Wasim Sajid -- 7. Nutritive and digestive effects of starch and fiber in whole wheat / Birger Svihus -- 8. Colorectal cancer prevention by wheat consumption: a three-valued logic - true, false, or otherwise? / Gabriel Wcislo, Katarzyna Szarlej-Wcislo -- 9. Whole grain and dietary fiber intake and risk of prostate cancer / Katharina Nimptsch -- 10. Bioactive phytochemicals in wheat bran for colon cancer prevention / Shengmin Sang, Yingdong Zhu -- 11. Immunologic reactions to wheat: celiac disease, wheat allergy and gluten sensitivity / Michelle Pietzak -- 12. Celiac disease and its therapy: current approaches and new advances / Vandana Nehra, Eric V. Marietta, Joseph A. Murray -- 13. Gluten metabolism in humans: involvement of the gut microbiota / Alberto Caminero, Esther Nistal, Alexandra R. Herr, Jenifer Pez-Andr, Luis Vaquero, Santiago Vivas, JosMar Ru{u2A7A} de Morales, Javier Casqueiro -- 14. Adverse reactions to gluten: exploitation of sourdough fermentation / Raffaella di Cagno, Carlo Giuseppe Rizzello, Marco Gobbetti -- 15. Antioxidant properties of wheat bran against oxidative stress / Masashi Higuchi -- 16. Wheat and rice dietary fiber in colorectal cancer prevention and the maintenance of health / Philip J. Harris, Lynnette R. Ferguson -- 17. Sensory, technological, and health aspects of adding fiber to wheat-based pasta / Mike J. Sissons, Christopher M. Fellows -- 18. Dietary fiber and wheat bran in childhood constipation and health / Helga Verena Leoni Maffei -- 19. Wheat bran and cadmium in human health / Tatiana Emanuelli, Bruna Gressler Milbradt, Maria da Gra{u3860}Kolinski Callegaro, Paula Rossini Augusti -- 20. Wheat contaminants (pesticides) and their dissipation during processing / Muhammad Atif Randhawa, Anwaar Ahmed, Muhammad Sameem Javed -- 21. Genetically modified rice with health benefits as a means to reduce micronutrient malnutrition: global staus, consumer preferences, and potential health impacts of rice biofortifcation / Hans de Steu, Joseph Birundu Mogendi, Dieter Blancquaert, Willy lambert, Dominque van der Straeten, Xavier Gellynck -- 22. Rice bran: a food ingredient with global public health opportunities / Erica C. Borresen, Elizabeth P. Ryan -- 23. Rice bran oil: benefits to health and applications in pharmaceutical formulations / Lucas Almeida Rigo, Adriana Raffin Pohlmann, Silvia Stanis{u3D61}ski Guterres, Ruy Carlos Ruver Beck -- 24. Rice intake, weight change and netabikuc syndrome / Zumin Shi, Anne W. Taylor, Gary A. Wittert -- 25. Glycemic index of Indian cereal staple foods and their relationship to diabetes and metabolic syndrome / Ruchi Vaidya, Viswanathan Mohan, Mookambika Ramya Bai, Sudha Vasudevan -- 26. Rice and type 2 diabetes / Akiko Nanri, Tetsuya Mizoue -- 27. Rice and the clycemic index / Un Jae Chang, Yang Hee Hong, Eun Young Jung, Hyung Joo Suh -- 28. Arsenic in rice: sources and human health risk / Mohammad Azizur Rahman, Mohammad Mahmudur Rahman, Ravi Naidu -- 29. Arsenic in rice-based infant foods / Sandra Munera-Picazo, Amanda Ram{u2A6D}Gandolfo, Claudia Cascio, Concha Casta-Iglesias, Antonio J. Signes-Pastor, Franciso Burl{u2BEC} Parvez I. Haris, {u206E}gel A. Carbonell-Barrachina -- 30. Inorganic arsenic in rice and rice bran: health implications / Suthep Ruangwises, Piyawat Saipan, Nongluck Ruangwises -- 31. Apoptosis and arabinoxylan rice bran / Mamdooh Helal Ghoneum -- 32. y-Oryzanol: an attractive bioactive component from rice bran / Christelle Lemus, Apostolis Angelis, Maria Halabalaki, Alexio Leandros Skaltsounis -- 33. Evaluation of physical and nutritional properties of extruded products based on brown rice and wild legume mixtures / Elena Pastor-Cavada, Silvina R. Drago, Rolando J. Gonzez -- 34. Rice bran antioxidants in health and wellness / Md. Shafiqul Islam, Naoki Matsuki, Reiko Nagasaka, Kazuyuki Ohara, Takamitsu Hosoya, Hiroshi Ozaki, Hideki Ushio, Masatoshi Hori -- 35. Organic rice bran oils in health / Khongsak Srikaeo -- 36. Fermented rice bran attenuates oxidative stress / Dongyeop Kim, Gi Dong Han -- 37. Rice bran oil's role in health and cooking / Abdul Rohman -- 38. Amino acid production from rice straw hydrolyzates / Christian Matano, Tobias M. Meiswinkel, Voker F. Wendisch -- 39. Germinated barley foodstuff dampens inflammatory bowel disease / Osamu Kanauchi, Keiichi Mitsuyama, Akira Andoh -- 40. Development of functional foods (enzyme-treated rice fiber) from rice by-products / Osamu Kanauchi, Muriel Larauche, Yvette Tach-- 41.Chickpea (Chicer arietinum L.) fortification of cereal-based foods to increase fiber and phytochemical content / Clara Fares, Valeria Menga.
Includes bibliographical references and index.
Keywords: Triticum; Dietary Fiber; Functional food; Health promotion; Oryza sativa